Bio-rational management of groundnut defoliators (Spodoptera litura and Helicoverpa armigera) in kharif season: Bio-rational management of groundnut defoliators (Spodoptera litura and Helicoverpa armigera) in kharif season - DAHIPHALE K D; S V WAGMARE; A K GHOTMUKALE; D P DESHPANDE (Journal of Oilseeds Research, 2023)
Field trial was laid at ORS, Latur (MS, India) to evaluate insecticides for the management of Helicoverpa armigera (Hubner) and Spodoptera litura (Fabricius) infesting groundnut. Insecticides/bioinsecticides evaluated were Bt-127 SC @3ml/lit, Delfin (Bt commercial formulation) @1g/lit, Quinalphos 25 EC @ 2ml/lit and Chlorantraniliprole 18.5 SC @ 0.3ml/lit. The results revealed that insecticidal treatments were significantly superior over untreated control in reducing the infestation groundnut defoliators. However, chlorantraniliprole 18.5 SC was significantly most effective as well as safer to natural enemies. Significantly higher pod yield (1672 kg/ha) of groundnut was recorded in treatment Chlorantraniliprole 18.5 SC @ 0.3ml/lit, and it was at par with treatment Bt127 SC @3ml/lit (1559 kg/ha).